Administrative procedures: essence and varieties - Осадчий, Анатолій Юрійович; Осадчий, А. Ю.; Осадчий, Анатолий Юрьевич; Osadchyi, Anatolii Yu.; Закаленко, Олена Василівна; Закаленко, О. В.; Закаленко, Елена Васильевна; Zakalenko, Olena V. (Riga : Izdevniecība “Baltija Publishing”, 2020)
The article is devoted to the disclosure of the essence and approaches to the classification of administrative procedures. This category is relativelynew to Ukrainian administrative law. Therefore, at the doctrinal level it still remains insufficiently studied. There is a lack of consensus on the understanding of the concept of administrative procedures and stable approaches to their systematization and classification, which is a necessary prerequisite for proper legal regulation and ensuring the effectivenessof administrative procedures in the mechanism of legal regulation. It is proposed to understand under the administrative procedures the definedby the law order of actions for implementing legal forms of public administration. Their characteristic features are identified, which allow to distinguish administrative procedures from other legal procedures. The main scientific approaches to the classification of administrative procedures are also studied. It is determined that the greatest theoretical and practical value has the division of administrative procedures by content – depending on which of the legal forms of the activity of public administration bodies they mediate.

Стаття присвячена розкриттю сутності та підходів до класифікації адміністративних процедур. Ця категорія є відносно новою для українського адміністративного права. Тому на доктринальному рівні все ще залишається недостатньо вивченою. Відсутній консенсус щодо розуміння поняття адміністративних процедур та стійких підходів до їх систематизації та класифікації, що є необхідною передумовою належного правового регулювання та забезпечення ефективності адміністративних процедур у механізмі правового регулювання. Під адміністративними процедурами пропонується розуміти визначений законом порядок дій щодо реалізації правових форм державного управління. Визначено їх характерні ознаки, які дозволяють відрізнити адміністративні процедури від інших правових процедур. Досліджено також основні наукові підходи до класифікації адміністративних процедур. Визначено, що найбільше теоретичне та практичне значення має поділ адміністративних процедур за змістом – залежно від того, яку з правових форм діяльності органів державного управління вони опосередковують.
Osadchyi A. Yu. Administrative procedures: essence and varieties / A. Yu. Osadchyi, O. V. Zakalenko // Public administration under modern conditions: concept, features, challenges : Collective monograph. - Riga : Izdevniecība “Baltija Publishing”, 2020. - P. 131-145.
Keywords: administrative procedures; classification of administrative procedures; doctrine of administrative law; адміністративні процедури; класифікація адміністративних процедур; доктрина адміністративного права; Research Subject Categories::LAW/JURISPRUDENCE::Public law::Administrative law